THE ROLE OF DIET IN PARKINSON'S DISEASE AND ITS ORGANIZATIONAL APPROACHES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article investigates the clinical and functional effectiveness of dietary therapy in patients with Parkinson's disease. A total of 65 patients participated in the study, divided into two groups: one received individualized dietary treatment, and the other served as a control group without dietary intervention. Results based on the UPDRS scale, gastrointestinal symptoms, SF-36 quality of life questionnaire, and antioxidant intake demonstrated that the dietary intervention group showed significant improvement in symptoms, digestive function, and quality of life. Dietary therapy is recognized as a valuable adjunct to conventional Parkinson's disease treatment strategies.